Influence Micro Teaching and PLP II on Interest in Becoming A Teacher Students of Accounting Education Muhammadiyah University Surakarta - Sari, Nanda Mita; Rohmah, Wafrotur (Universitas Muhammadiyah Surakarta, 2023)
The purpose of this study was to determine: (1) the effect of micro teaching on the interest in becoming a teacher, (2) the effect of the introduction of the school field II (PLP II) on the interest in becoming a teacher, (3) the effect of micro teaching and the introduction of the school field II (PLP II) ) on the interest in becoming a teacher for Accounting Education students at the Muhammadiyah University of Surakarta. This research was conducted at the Muhammadiyah University of Surakarta which is located at Jl. A. Yani Tromol Post 1, Pabelan, Kartasura, Surakarta. This research method uses quantitative methods with a survey design. The population in this study were all 148 students of the Accounting Education Study Program class of 2019 Muhammadiyah University of Surakarta. The sample is 108 students with simple random sampling technique. The data collection technique uses a questionnaire with the help of Google from. The data analysis technique used is multiple linear regression, t test, F test, test the coefficient of determination, effective contribution (SE) and relative contribution (SR). The results of this study indicate that: 1) Micro teaching has a positive and significant effect on the interest in becoming a teacher. This can be seen from the calculation results which show that 2.343 > 1.659 and a significance value < 0.05, namely 0.008; 2) The introduction of schooling field II (PLP II) has a positive and significant effect on the interest in becoming a teacher. This can be seen from the calculation results which show that 2.594 > 1.659 and a significance value < 0.05, namely 0.001; 3) Micro teaching and introduction to the field of schooling II (PLP II) simultaneously influence the interest in becoming a teacher. This can be seen from the calculation results which show that 10.473 > 3.08 and a significance value < 0.05, which is 0.000.